2006
DOI: 10.1002/bmc.691
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatographic-electrospray tandem mass spectrometric determination of clarithromycin in human plasma

Abstract: A rapid, sensitive and specific LC-MS-MS method has been developed for the determination of clarithromycin (CLA) in human plasma using roxithromycin (ROX) as the internal standard. Samples were prepared via liquid-liquid extraction with methyl tert-butyl ether (MTBE) and chromatographed on a Supelco RP 18 (4.6 × 50 mm, 3 µm particle size) column with a mobile phase consisting of acetonitrile:methanol:60 mM (pH 3.5) ammonium acetate buffer (32.5:32.5:35) at a constant flow rate of 0.8 mL/min. The run time was 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Stability experiments have therefore to be performed in the local setting during method development. Samples should be protected from light and be analyzed directly or frozen at −20 • C. Although, ranges of the calibration curves are sometimes wider [17,23], in our study these were based on the expected plasma concentrations of the components (depending on the dose and individual variation) and on the MIC of Mycobacterium ulcerans. Much lower LLOQs do not contribute significantly to the area under the concentration time curve and require liquid-liquid extraction (LLE) [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stability experiments have therefore to be performed in the local setting during method development. Samples should be protected from light and be analyzed directly or frozen at −20 • C. Although, ranges of the calibration curves are sometimes wider [17,23], in our study these were based on the expected plasma concentrations of the components (depending on the dose and individual variation) and on the MIC of Mycobacterium ulcerans. Much lower LLOQs do not contribute significantly to the area under the concentration time curve and require liquid-liquid extraction (LLE) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Samples should be protected from light and be analyzed directly or frozen at −20 • C. Although, ranges of the calibration curves are sometimes wider [17,23], in our study these were based on the expected plasma concentrations of the components (depending on the dose and individual variation) and on the MIC of Mycobacterium ulcerans. Much lower LLOQs do not contribute significantly to the area under the concentration time curve and require liquid-liquid extraction (LLE) [17]. Due to the observed carryover of rifampicin the calibration range had to be narrowed compared to the method of analysis of Hartkoorn et al [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature survey revealed that various methods have been developed for the estimation of clarithromycin from laboratory prepared mixtures, pharmaceutical preparations and biological matrices (such as human plasma) through automated solid phase extraction and electrochemical detection, liquid chromatographic electrospray tandem mass spectrometry and high performance liquid chromatography. [4][5][6][7] But most of these reported methods were cumbersome due to poor resolution, troublesome mobile phase (buffers) preparation and lengthy run time, hence difficult for routine analysis. Therefore, the aim of the present work was to establish a rapid, simple, precise, specific, accurate, and cost-effective RP-HPLC method according to ICH guidelines Q2 (R1) for routine analysis of clarithromycin in pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Various analytical methods have been developed to determine clarithromycin in formulations and biological samples, such as high-performance liquid chromatography (HPLC) with fluorescent [3], ultraviolet [4,5], electrochemical [6][7][8][9][10][11][12][13][14][15][16][17], amperometric [18] and mass spectrometric detection [19][20][21][22][23][24]. The fluorescence detection method [3] needs derivatization before the analysis.…”
Section: Introductionmentioning
confidence: 99%